2017
DOI: 10.1111/bph.13754
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish models in neuropsychopharmacology and CNS drug discovery

Abstract: Despite the high prevalence of neuropsychiatric disorders, their aetiology and molecular mechanisms remain poorly understood. The zebrafish (Danio rerio) is increasingly utilized as a powerful animal model in neuropharmacology research and in vivo drug screening. Collectively, this makes zebrafish a useful tool for drug discovery and the identification of disordered molecular pathways. Here, we discuss zebrafish models of selected human neuropsychiatric disorders and drug-induced phenotypes. As well as coverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 262 publications
(371 reference statements)
3
100
0
Order By: Relevance
“…Since about one-third of patients show no significant improvement in current therapeutic treatments [2], there is a clear need for a better understanding of the disease and for more effective drugs. Zebrafish is an emerging model for the study of human neurological disorders, and for the identification of potential therapeutic targets [3,4]. Although the Central Nervous Systems (CNS) of mammalian and teleost display considerable neuroanatomical differences, several fundamental principles of brain development and function are evolutionarily well conserved [5], thus allowing to recapitulate in the fish many mechanisms and clinical features of brain disorders [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since about one-third of patients show no significant improvement in current therapeutic treatments [2], there is a clear need for a better understanding of the disease and for more effective drugs. Zebrafish is an emerging model for the study of human neurological disorders, and for the identification of potential therapeutic targets [3,4]. Although the Central Nervous Systems (CNS) of mammalian and teleost display considerable neuroanatomical differences, several fundamental principles of brain development and function are evolutionarily well conserved [5], thus allowing to recapitulate in the fish many mechanisms and clinical features of brain disorders [6].…”
Section: Introductionmentioning
confidence: 99%
“…The use of zebrafish in the field of neuroscience continues to increase and a number of recent reviews have highlighted both the strengths and weaknesses of using zebrafish to study neuroactive compounds and brain disorders [9][10][11][12][13][14][15]. The zebrafish brain has many analogous regions to those of higher vertebrates and the complexity of both juvenile and adult zebrafish brains has been well documented [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that zebrafish are sensitive to a large number of neurotropic drugs including: antipsychotics, mood stabilizers, anxiolytics, antidepressants, ethanol, hypnotics, stimulants, hallucinogens, antiepileptics, analgesics and cognitive enhancers [15,16]. In addition, both adult and larval zebrafish can be used to model numerous neural disorders including pain/nociception, anxiety, stress, PTSD, ADHD, Autism, epilepsy, learning & memory deficits, psychiatric disorders, Alzheimer's disease, amyotrophic lateral sclerosis (ALS), Parkinson's disease, schizophrenia, bi-polar disorder, addiction and brain cancer [6,9,11,[14][15][16][20][21][22][23][24][25]. This provides in vivo models with which to test not only the bioactivity of various neuroactive compounds, but also allows for the testing of their potential efficacy against numerous models of disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in order to provide information about their functional activity, we performed an innovative functional analysis by utilizing zebrafish embryo (Danio rerio), to compare the effect of the drugs on immune system cell activation. Recently, zebrafish has become a very interesting animal model in different fields, including pharmacology and toxicology [21][22][23][24][25][26][27][28]. Aside from small molecule discovery and screening, it is now used for complex biological drugs characterization, such as biosimilars [29,30].…”
Section: Introductionmentioning
confidence: 99%